If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x = -6 Solving 3 + 5x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = -6 + -3 5x = -6 + -3 Combine like terms: -6 + -3 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8
| 3(5+7)= | | 1v+5v=12 | | 8(4+9)= | | 6n+-14n+6n+-1=-15 | | (7q-3q^3)+(16-8q^3+5q^2-q)= | | 6n+-14n+6n+-1=15 | | 5(2+4)= | | -25x^2=100 | | 8h+-7h+3h=16 | | (6m^3-5)-(m^3+4m^2-9m-2)= | | -2x-8=3 | | 6h+-11h=-15 | | 36=3(-2x) | | -6(2h+8)+7= | | 4h+-1h+-3h+-1h=5 | | 5x^2=45x | | 10w-145=955 | | 2x+1=x+3 | | -10n+7n+-15=9 | | x+(2x+21)=180 | | 214=6n+19 | | 2(-1)= | | 2(4-2x)=22 | | 3(2x-3)=15 | | z^3+343=0 | | 6x-7w= | | 2q+8q-4=6 | | x^2+18x-448=0 | | 4x^2-19x+18=-4x+4 | | r^3=36 | | 6x^2-13x-63=0 | | 7x-2+3x=4+2x-2 |